Checklist of Benthic Cnidaria in the SW Atlantic Ocean (54ºS–56ºS) - Schejter, L.; Genzano, G.; Pérez, C.d.; Acuña, F.; Cordeiro, R.t.s.; Silva, R.a.; Garese, A.; Bremec, C. S. (Zootaxa, 2020)
In this study we provide an updated checklist of benthic Cnidaria from SW Atlantic Ocean that comprised the Marine Protected Areas Namuncurá I and II, located at Burdwood bank, and other neighbouring locations. A total of 88 taxa was recorded: 36 hydrozoans and 52 anthozoans from which 32 were octocorals, 10 scleractinian corals, 8 sea anemones and 2 zoanthids. Burdwood bank presented the highest richness considering that 87% of the recorded species inhabit this plateau or its slope. Besides some common species widely distributed in the studied sub-areas, at least 24 species represent new distributional records while few were exclusively recorded at Burdwood bank. The inventory here provided will help to identify key habitat-forming species in a complex habitat where marine animal forests and vulnerable marine ecosystems were previously detected. It will be also a very valuable tool for the management and monitoring of the sub-areas under protection.